Characterization of dynamic stall of a wind turbine airfoil with a high Reynolds number - H. R. Kim; J. A. Printezis; J. D. Ahrens; J. R. Seume; L. Wein (Wind Energy Science)
This study shows an extensive analysis of dynamic stall on wind turbine airfoils, preparing for the development of a reduced-order model applicable to thick airfoils (t/c>0.21<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="53pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="aa10b0f7589f34c39cbb1ba9f034335d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="wes-10-161-2025-ie00001.svg" width="53pt" height="14pt" src="wes-10-161-2025-ie00001.png"/></svg:svg>) in the future. Utilizing unsteady Reynolds-averaged Navier–Stokes (URANS) simulations of a pitching FFA-W3-211 airfoil with a Reynolds number of 15 × 106, our analysis identifies the distinct phases in the course of the evolution of dynamic stall. While the dynamic stall is conventionally categorized into the primary-instability transitioning to the vortex formation stage, we suggest two sub-categories for the first phase and an intermediate stage featuring a plateau in lift prior to entering the full stall region. This delays the inception of deep stall, approximately 3° for a simulation case. This is not predictable with existing dynamic-stall models, which are optimized for applications with a low Reynolds number. These features are attributed to the enhanced flow attachment near the leading edge, restricting the stall region downstream of the position of maximum thickness. The analysis of the frequency spectra of unsteady pressure confirms the distinct characteristics of the leading-edge vortex street and its interaction with large-scale mid-chord vortices in forming the dynamic-stall vortices (DSVs). Examination of the leading-edge suction parameter (LESP) proposed by Ramesh et al. (2014) for thin airfoils with low Reynolds numbers reveals that the LESP is a valid criterion in predicting the onset of the stall for thick airfoils with high Reynolds numbers. Based on the localized separation behavior during a dynamic-stall cycle, we suggest a mid-chord suction parameter (MCSP) and trailing-edge suction parameter (TESP) as supplementary criteria for the identification of each stage. The MCSP exhibits a breakdown in magnitude at the onset of the dynamic-stall formation stage and full stall, while the TESP supports indicating the emergence of a full stall by detecting the trailing-edge vortex.